2019
DOI: 10.1051/e3sconf/201910900010
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of technogenic load from sludge collectors due to separation and dehydration of the stored material

Abstract: Purpose: the identification of geomechanical problems of mining industry wastes accumulation and substantiation of the ways for their solution with the possibility of processing the watery technogenic feedstock. It has been shown that in order to reduce the technogenic load, it is necessary to reduce the area of land under the waste ponds and the accumulated volumes themselves of mining and enrichment wastes. It has been revealed that the mineral stock, formed from wide grain-size classes with a high content o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Parameters of enrichment waste hydraulic transport and features of handling particles in a turbulent state are given in [7]. The paper [3] substantiates the possibility of processing water man-made raw materials. When processing man-made raw materials, the main problem is the processing of the fine fraction.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Parameters of enrichment waste hydraulic transport and features of handling particles in a turbulent state are given in [7]. The paper [3] substantiates the possibility of processing water man-made raw materials. When processing man-made raw materials, the main problem is the processing of the fine fraction.…”
Section: Introductionmentioning
confidence: 74%
“…As a result, it is concluded that it is better to mine storage tanks instead of building dams. In work [3], technical solutions for re-excavation of man-made mass or clearing are proposed, and technological schemes are developed. The authors made a justified decision to reduce the man-made load by reducing the area of the territories under the sedimentation tanks.…”
Section: Introductionmentioning
confidence: 99%